Strategi Peningkatan Keterampilan Menulis Akademik Mahasiswa melalui Penggunaan Media Digital - Irawati, Wa Ode; Malabar, Sayama; Mangilo, Nurhalima (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
This study aims to identify and formulate effective strategies to enhance university students' academic writing skills through the integration of digital media in Indonesian language instruction. Employing a literature review method, this article analyzes relevant literature on digital media, learning strategies, and the theoretical frameworks of constructivism and TPACK. The findings indicate that platforms such as Google Docs, Grammarly, Mendeley, and Padlet significantly support all stages of academic writing, from pre-writing to publication. Recommended strategies include blended learning, project-based learning, and problem-based digital literacy training. The integration of digital media enhances interactivity, reflection, collaboration, and the academic quality of students' writing. These findings underscore the importance of aligning technology, pedagogy, and content in designing effective and relevant writing instruction in the digital era.